Low risk of inhibitor formation in haemophilia patients after a change in treatment from Chinese hamster ovary cell-produced to baby hamster kidney cell-produced recombinant factor VIII - Singleton, Evelyn; Smith, Jude; Kavanagh, Mary; Nolan, Beatrice; White, Barry (Thrombosis and Haemostasis, 2007)
This retrospective survey of haemophilia A patients from multiple treatment centres in Ireland assessed the development of inhibitors following a switch in the prescribed treatment from recombinant factor VIII (rFVIII) produced by Chinese hamster ovary (CHO) cells (rFVIII-CHO) to rFVIII produced by baby hamster kidney (BHK) cells (rFVIII-BHK). Ninety-four patients participated in the survey. Most patients (89.4%) had severe haemophilia. One of 77 (1.3%) patients with no inhibitor history developed an inhibitor. This was a patient with moderate haemophilia A who developed a transient, low-titre (1 BU) de novo inhibitor following surgery. Recurrent inhibitors were detected in three of 17 patients with an inhibitor history during the 20-month post-switch study period. All patients continued on rFVIII-BHK therapy, and all tested negative for inhibitors at the time of their last inhibitor assay during the observation period. These results are consistent with the low levels of inhibitor formation demonstrated in phase III studies of previously treated patients receiving BHK-produced rFVIII and support the low risk of inhibitor formation following a change from rFVIIICHO to rFVIII-BHK.
Keywords: Recombinant factor VIII; FVIII inhibitor; FVIII-CHO; FVIII-BHK